Thin Film Co3O4/TiO2 Heterojunction Solar Cells. Issue 1 (13th August 2014) - Kupfer, Benjamin; Majhi, Koushik; Keller, David A.; Bouhadana, Yaniv; Rühle, Sven; Barad, Hannah Noa; Anderson, Assaf Y.; Zaban, Arie
<x xml:space="preserve">Abstract</x> Co3O4 is investigated as a light absorber for all‐oxide thin‐film photovoltaic cells because of its nearly ideal optical bandgap of around 1.5 eV. Thin film TiO2/Co3O4 heterojunctions are produced by spray pyrolysis of TiO2 as a window layer, followed by pulsed laser deposition of Co3O4 as a light absorbing layer. The photovoltaic performance is investigated as a function of the Co3O4 deposition temperature and a direct correlation is found. The deposition temperature seems to affect both the crystallinity and the morphology of the absorber, which affects device performance. A maximum power of 22.7 μW cm−2 is obtained at the highest deposition temperature (600 °C) with an open circuit photovoltage of 430 mV and a short circuit photocurrent density of 0.2 mA cm−2. Performing deposition at 600 °C instead of room temperature improves power by an order of magnitude and reduces the tail states (Urbach edge energy). These phenomena can be explained by larger grains that grows at high temperature, as opposed to many nucleation events that occur at lower temperature.